The Effect of Job Stress on Turnover Intention at SIX SENSES Uluwatu, Bali - Juniastuti, Ni Made; Sulistyawati, Ni Luh Ketut Sri; Jata, I Wayan (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Human resources are an important aspect that determines the success of a company in achieving its goals. However, companies often face problems such as turnover intention, which is the willingness of employees to change jobs. This study aims to examine the effect of work stress on turnover intention at Six Senses Uluwatu, Bali. A total of 74 respondents were selected through a purposive sampling method. Data were collected using a 5-point Likert scale questionnaire with 30 statements. Data analysis was carried out using the classical assumption test, simple linear regression, t-test, and coefficient of determination with SPSS 24 Windows version. The results showed that work stress had a positive and significant effect on turnover intention, with a tcount>ttable value of 15,409> 1,996 and a significance value of 0.000 <α<0.05. Work stress contributed 76.7% to turnover intention. This study is the basis for evaluating employee work stress.